Sea monsters don't ride motorcycles - Dadey, Debbie (Dadey, Debbie. Adventures of the Bailey School kids, 2000)
"There are some pretty weird grown-ups living in Bailey City. But is the winning rider at the motorcycle races really a sea monster? The Bailey School kids are going to find out!"--Cover.